Photoactive RuII-polypyridyl complexes that display sequence selectivity and high-affinity binding to duplex DNA through groove binding - Ghosh, Amrita; Das, Priyadip; Gill, Martin R.; Kar, Prasenjit; Walkar, Michael G.; Thomas, Jim A.; Das, Amitava (Chemistry A European Journal, 2011)
The duplex-DNA binding properties of a nonintercalating polypyridyl ruthenium(II) complex that incorporates a linear extended ligand with a catechol moiety has been probed with a variety of photo- and biophysical techniques. These studies reveal that the complex groove binds to DNA sequences biphasically, and displays binding constants equivalent to those of high-affinity metallointercalators. The complex also displays preferential binding to AT-rich sequences. Changes in the structure of the coordinated catechol ligand and the incorporation of intercalating ancillary ligands into the complex were found to modulate both the optical-binding response and binding parameters of the system, which indicates that the catechol moiety plays a crucial role in the observed enhancement to binding affinities.

Cytostatic ruthenium(II)-platinum(II) bis(terpyridyl) anticancer complex that blocks entry into sphase by up-regulating p27(KIP1) - Ramu, Vadde; Gill, Martin R.; Jarman, Paul J.; Turton, David; Thomas, Jim A.; Das, Amitava; Smythe, Carl (Chemistry-A European Journal, 2015)
Cytostatic agents that interfere with specific cellular components to prevent cancer cell growth offer an attractive alternative, or complement, to traditional cytotoxic chemotherapy. Here, we describe the synthesis and characterization of a new binuclear Ru-II-Pt-II complex [Ru(tpy)(tpypma)Pt(Cl)(DMSO)](3+) (tpy=2,2:6,2-terpyridine and tpypma=4-([2,2:6,2-terpyridine]-4-yl)-N-(pyridin-2-ylmethyl)aniline), VR54, which employs the extended terpyridine tpypma ligand to link the two metal centres. In cell-free conditions, VR54 binds DNA by non-intercalative reversible mechanisms (K-b=1.3x10(5)M(-1)) and does not irreversibly bind guanosine. Cellular studies reveal that VR54 suppresses proliferation of A2780 ovarian cancer cells with no cross-resistance in the A2780CIS cisplatin-resistant cell line. Through the preparation of mononuclear Ru-II and Pt-II structural derivatives it was determined that both metal centres are required for this anti-proliferative activity. In stark contrast to cisplatin, VR54 neither activates the DNA-damage response network nor induces significant levels of cell death. Instead, VR54 is cytostatic and inhibits cell proliferation by up-regulating the cyclin-dependent kinase inhibitor p27(KIP1) and inhibiting retinoblastoma protein phosphorylation, which blocks entry into Sphase and results in G1 cell cycle arrest. Thus, VR54 inhibits cancer cell growth by a gain of function at the G1 restriction point. This is the first metal-coordination compound to demonstrate such activity.
Keywords: antitumor agents; cytostatic; p27KIP1; platinum drugs; ruthenium terpyridine

Photo-induced cytotoxicity and anti-metastatic activity of ruthenium(II)-polypyridyl complexes functionalized with tyrosine or tryptophan - Ramu, Vadde; Aute, Sunil; Taye, Nandaraj; Guha, Rweetuparna; Walker, Michael G.; Mogare, Devaraj; Parulekar, Apoorva; Thomas, Jim A.; Chattopadhyay, Samit; Das, Amitava (Dalton Transactions, 2017)
The synergistic effect of oxygen, light, and photosensitizer (PS) has found applications in medicine for the treatment of cancer through photodynamic therapy (PDT). Induction of apoptosis to cancerous cells will prevent tumor metastasis that spreads cancer cells to the neighboring organs/tissues. Herein, we report the two apoptotic Ru(II)-polypyridyl complexes that are functionalized with pendant amino acid moieties tyrosine (1) and tryptophan (2), respectively. These two water soluble complexes were found to interact strongly (K-a(1) = (1.18 +/- 0.28) x 10(5) M-1 and K-a(2) = (1.57 +/- 0.77) x 10(5) M-1) with CT-DNA. Isothermal titration calorimetry (ITC) studies revealed that these complexes bind to CT-DNA through an entropically driven process. Both the complexes showed photo-induced cytotoxicity and exhibit apoptotic activity under photo-irradiation conditions. The comet assay indicated that these complexes can damage cellular DNA, which is attributed to the significant build-up of O-1(2) level even on irradiation with low intensity light (10 J cm(-2), lambda(Range) 450-480 nm). This photoinduced DNA damage and apoptosis in A549 cells was induced by reactive oxygen species (ROS) and occurred through up-regulation of apoptotic marker caspase-3. Control experiments under dark conditions revealed an insignificant cytotoxicity towards these cells for two photosensitive molecules.

Ratiometric sensor for DNA based on a dual emission Ru(dppz) light-switch complex - Walker, Michael G.; Ramu, Vadde; Meijer, Anthony J. H. M.; Das, Amitava; Thomas, Jim A. (Dalton Transactions, 2017)
Herein we describe the DNA binding properties of two new water-soluble ruthenium complexes; experimental and computational data reveal that both complexes display dual emission from MLCT and LLCT excited states. The interaction of the new complexes with DNA was also investigated. Although one of the complexes only binds DNA though groove binding, the second complex has separate ligands capable of groove binding and intercalation. Nevertheless, it was found that both complexes interact with duplex DNA with high affinity. DNA induced distinctive changes in the emission of the complexes; although the groove binding complex only displays a modest increase in emission on binding, the complex that contains the intercalating Ru-II(dppz) moiety displays a large increase in MLCT-based emission on DNA binding while emission from the LLCT excited state is unaffected. This means that the complex functions as the first ratiometric sensor for DNA.

Super-resolution probe to monitor HNO levels in the endoplasmic reticulum of cells - Ali, Firoj; Sreedharan, Sreejesh; Ashoka, Anila Hoskere; Saeed, Hiwa K.; Smythe, Carl G. W.; Thomas, Jim A.; Das, Amitava (Analytical Chemistry, 2017)
Selective detection of nitroxyl (HNO), which has recently been identified as a reactive nitrogen species, is a challenging task. We report a BODIPY-based luminescence ON reagent for detection of HNO in aqueous solution and in live RAW 264.7 cells, based on the soft nucleophilicity of the phosphine oxide functionality toward HNO. The probe shows high selectivity to HNO over other reactive oxygen/nitrogen and sulfur species. Luminescence properties of the BODIPY-based chemodosimetric reagent make it an ideal candidate for use as a reagent for super-resolution structured illumination microscopy. The viability of the reagent for biological in vivo imaging application was also confirmed using Artemia as a model.

Polysulfide-triggered fluorescent indicator suitable for super-resolution microscopy and application in imaging - Hoskere, Anila A.; Sreedharan, Sreejesh; Ali, Firoj; Smythe, Carl G.; Thomas, Jim A.; Das, Amitava (Chemical Communications, 2018)
A new physiologically benign and cell membrane permeable BODIPY based molecular probe, MB-S-n, specifically senses intracellular hydrogen polysulfides (H2Sn, n > 1) localized in the endoplasmic reticulum. This reagent is suitable for mapping the intracellular distribution of H2Sn by wide-field as well as super-resolution Structured Illumination Microscopy (SIM).

Tracking HOCl concentrations across cellular organelles in real time using a super resolution microscopy probe - Ali, Firoj; Aute, Sunil; Sreedharan, Sreejesh; Anila, H. A.; Saeed, Hiwa K.; Smythe, Carl G.; Thomas, Jim A.; Das, Amitava (Chemical Communications, 2018)
BODIPY derivative, SF-1, exclusively shows a fluorescence ON response to HOCl and images endogenously generated HOCl in RAW 264.7 macrophages. Widefield and super resolution structured illumination microscopy images confirm localization in the Golgi complex and lysosomes, and hence specifically detects HOCl generated in these organelles. SF-1 is compatible with 3D-SIM imaging of individual cells.